KELEMBAGAAN DAN KEMANDIRIAN PETANI DALAM PEMBANGUNAN PERTANIAN INSTITUTION AND INDEPENDENCE OF FARMERS IN AGRICULTURAL DEVELOPMENT - Afrizal Malik (Fakultas Pertanian, Universitas Janabadra, 2023)
Urgensi eksistensi kelembagaan petani dalam pembangunan pertanian di Indonesia, kemandirian petani, dan strategi dalam pengembangan kelembagaan petani sehingga mampu menjadi sarana untuk mewujudkan petani yang mandiri. Keberadaan kelembagaan petani bagi petani sudah menjadi keniscayaan untuk memperbaiki taraf hidup, harkat dan martabatnya. Kelembagaan petani harus ditempatkan sebagai sarana untuk mewujudkan harapan, keinginan, dan pemenuhan kebutuhan petani. Kelembagaan petani yang efektif diharapkan mampu memberi kontribusi yang nyata dalam meningkatkan kemandirian dan martabat petani. Peningkatan kapasitas kelembagaan petani dilakukan sejalan dengan kegiatan penyuluhan pertanian dengan memotivasi petani untuk berpartisipasi dalam kelembagaan petani. Penyuluhan pertanian perlu dirancang dengan memberikan muatan pada penguatan kapasitas individu petani sekaligus penguatan kapasitas kelembagaan petani. Upaya yang sebaiknya dilakukan oleh pihak-pihak pemangku kepentingan, terutama pemerintah adalah: (1) Meningkatkan kapasitas para penyuluh lapangan, (2) Menggunakan cara-cara atau pendekatan partisipatif yang orientasi pada kebutuhan petani dalam melakukan kegiatan penyuluhan, dan (3) Memperkuat kelembagaan penyuluhan.The urgency of the existence of farmer institutions in agricultural development in Indonesia, farmer independence, and strategies in developing farmer institutions so that they can become a means to realize independent farmers. The existence of farmer institutions for farmers has become a necessity to improve their standard of living, their dignity and worth. Farmers' institutions must be placed as a means to realize the hopes, desires, and fulfillment of farmers' needs. Effective farmer institutions are expected to be able to make a real contribution in increasing the independence and dignity of farmers. Increasing the institutional capacity of farmers is carried out in line with agricultural extension activities by motivating farmers to participate in farmer institutions. Agricultural extension needs to be designed to provide content on strengthening the capacity of individual farmers as well as strengthening the institutional capacity of farmers. Efforts that should be carried out by stakeholder parties, especially the government are: (1) Increasing the capacity of field extension workers, (2) Using participatory methods or approaches that are oriented to the needs of farmers in carrying out extension activities, and (3) Strengthening institutions counseling.